Emerging role of HJURP as a therapeutic target in cancers - Jiaqi Tan; Lertnimitphun Peeraphong; Chattarin Ruchawapol; Juan Zhang; Juan Zhao; Wenwei Fu; Li Zhang; Hongxi Xu (Acta Materia Medica)
Holliday junction recognition protein (HJURP) is a key molecular chaperone for centromere protein A (CENP-A), which is essential for chromosome separation during mitosis and cell cycle regulation. Recent studies have identified the essential role of HJURP in carcinogenesis. Abnormal upregulation of HJURP expression has been observed in various human cancers, such as non-small cell lung cancer (NSCLC), hepatocellular carcinoma (HCC), bladder cancer, and breast cancer, and is associated with poor pathologic development and prognosis. In vitro and in vivo studies have shown that HJURP mainly exerts oncogenic functions by regulating the cell cycle, cellular senescence, and epithelial-mesenchymal transition (EMT). The purpose of this review was to evaluate the prognostic significance of HJURP in human cancers and summarize anti-tumor studies targeting HJURP. The factors regulating HJURP in carcinogenesis and the corresponding effects are also discussed to provide new insight into targeting HJURP as a promising strategy for cancer treatment.